Use of herbicides on turfgrass - McElroy,J.S. (2013)
In crop production, weeds must be controlled so as not to adversely affect crop yield and crop quality. Thus, a low level of weeds infesting a field, in most instances, is not a problem. Except in sod or seed production, turfgrass does not have a yield component. The value of turfgrass is its inherent aesthetic quality and usability. Aesthetic quality is the beauty and value that turfgrass adds to a managed landscape. Usability can be the durability of a sport field, trueness of golf putting green roll, or reduction in soil loss from water runoff or wind. Any weed presence in turfgrass can decrease the aesthetic quality and usability of turfgrass. Utilizing herbicides is the only way to completely control weeds in a turfgrass stand. While it is possible to reduce weed populations using cultural or mechanical management practices, it is impossible to completely eliminate weeds as can be accomplished with herbicides. This manuscript will review the major herbicides used in turfgrass in the United States with respect to their modes of action, herbicide family, and primary use in turfgrass.